New Documents for the Biography of the Historian A. H. Slyusarsky (1900/1901–1980). - Protsenko , Mykhailo (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2025)
Research aim. To review and analyse the documents from the postgraduate file of A. H. Sliusarskyi, Doctor of Historical Sciences, Professor, long-time Dean (1947–1962) of the History Department of the O. M. Gorky Kharkiv State University (nowadays – V. N. Karazin Kharkiv National University).Methodology. The article was based on general scientific methods of analysis and synthesis, as well as special historical methods: historical and biographical, historical and comparative, and historical and typological methods.Scientific novelty. The introduction into scientific circulation of new documents found in the Archives of V. N. Karazin Kharkiv National University, which allow us to reconstruct part of the postgraduate years of A. H. Slyusarsky's life in Kharkiv, in particular, the preparation for the defence of his dissertation research on the topic: “Committees of Poor Peasants of Ukraine in 1920–1921 (before the NEP)”. The file contains his autobiography, a sheet reflecting his work history, etc.Conclusions. All documents in this file can be divided thematically into those devoted to his biography, official documents on his dissertation defence, and correspondence (in particular, a letter to the vice-rector for scientific work of the university I. M. Bulankin). These materials are not arranged in the file in chronological order. It can be assumed that this is due to the fact that during the Second World War the university was evacuated to Kzyl-Orda (Kazakhstan), and certain documents might not have been preserved in A. H. Sliusarsky's pre-war postgraduate file, so it was collected anew after the university returned to Kharkiv in 1943. Taken together, such biographical documents provide valuable information about his life and work, as well as clarify the mechanisms of dissertation defence during the Second World War. Anton Hryhorovych is an example of a person who, despite life's obstacles, pursued his goal and achieved it.